2022
DOI: 10.3389/fnmol.2022.818390
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Dimorphic Synapse: From Spine Density to Molecular Composition

Abstract: A synaptic sexual dimorphism is relevant in the context of multiple neurodevelopmental, neurodegenerative, and neuropsychiatric disorders. Many of these disorders show a different prevalence and progression in woman and man. A similar variance is also present in corresponding animal models. To understand and characterize this dimorphism in pathologies it is important to first understand sex differences in unaffected individuals. Therefore, sexual differences have been studied since 1788, first focusing on brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 179 publications
(193 reference statements)
0
7
0
1
Order By: Relevance
“…Sex differences have been reported in the brain that are independent of gonadal hormone levels ( Ingalhalikar et al, 2014 ; Pandya et al, 2019 ; Gegenhuber and Tollkuhn, 2020 ; Williams et al, 2021 ). Among them, differences in inhibitory synaptic transmission appear to be important ( Uhl et al, 2022 ). The excitability of a neural circuit is controlled by excitatory pyramidal neurons and inhibitory interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences have been reported in the brain that are independent of gonadal hormone levels ( Ingalhalikar et al, 2014 ; Pandya et al, 2019 ; Gegenhuber and Tollkuhn, 2020 ; Williams et al, 2021 ). Among them, differences in inhibitory synaptic transmission appear to be important ( Uhl et al, 2022 ). The excitability of a neural circuit is controlled by excitatory pyramidal neurons and inhibitory interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Memory impairment induced by normal age or age-related diseases is the primary neurodegenerative symptom leading to biochemical changes in some brain regions, an imperative structure among which is the hippocampus ( Wang et al, 2020 ). And the hippocampus is a brain region that is extremely sensitive to E2 ( Uhl et al, 2022 ). Immunohistochemical studies in the rodent brain show that GPER is colocalized with pyramidal cells in every region of the hippocampus (CA1-3) and granule cells in the dentate gyrus (DG) and is especially dense in the stratum lucidum of CA3 ( Waters et al, 2015 ; Mahmoud et al, 2016 ).…”
Section: Expression In Memory-related Tissues and Subcellular Distrib...mentioning
confidence: 99%
“…Neurotransmitters are essential for cell migration due to its chemotropic effects on migrating neurons (Behar et al, 1996), and there is abundant evidence that neurotransmitters and their receptors modulate gene expression through calcium and CREB signaling pathways impacting on neurogenesis, neuronal differentiation and programmed cell death (Jagasia et al, 2009;Ascenzi and Bony, 2017). Studies with animal models have demonstrated neurochemical differences between males and females, mostly due to sex hormones action (Uhl et al, 2022), and our results corroborate the hypothesis that during corticogenesis estrogen is a relevant signaling molecule (Denley et al, 2018). In a similar fashion, cytokines are critical signaling factors for the renewal of neural stem cells, regulation of differentiation between neurons and glial cells, determination of neuronal identity, and chemotropism, modifying cell migration and axon guidance (Deverman and Patterson, 2009).…”
Section: Figurementioning
confidence: 99%